Penentuan Marka Genetik Escherichia coli O157:H7 Asal Hewan dan Manusia dengan Metode Random Amplified Polymorphic DNA (GENETIC MARKERS IDENTIFICATION OF ESCHERICHIA COLI O157:H7 ORIGINATED FROM ANIMALS AND HUMAN BY USING RANDOM AMPLIFIED POLYMORPHIC DNA - Suardana, I Wayan; Widiasih, Dyah Ayu; Pinatih, Komang Januartha Putra (Jurnal Veteriner, 2014)
The use of random amplified polymorphic DNA (RAPD) as a method to identify a genetic markerof bacteria is widely used by researcher. This method is known as a simple, faster, and reliabletechnicque. This study is to find out the aplication of RAPD method in order to identify specific markersof E. coli O157:H7 as a zoonotic agent. The study began by cultivating of 20 isolates of E. coli O157:H7colected by previous study that consist of 2 isolates originated from cattle feces, 2 isolates originatedfrom beef, 2 isolates originated from chicken feces, 2 isolates originated from healthy human and 11isolates originated from unhealthy human (human with kidney failure). All isolates were confirmed byculturing on selective medium sorbitol MacConkey agar (SMAC). Confirmation were followed by testingon O157 latex aglutination, and finally by testing on H7 antiserum. RAPD method as molecularanalysis was performed using decamer primers mixture OPA-01, OPA-02, OPA-03, and OPA-04.Results of study showed both bands 1721 and 700 bp are specifically to differentiate of isolatesoriginated from cases of healthy and unhealthy human. On the other hand, bands with position 1721 bp,300 bp, and 250 bp indicate the isolates originated from unhealthy human, healthy human and chicken,respectively. Isolates from beef are characterized by both bands 1400 and 429 bp, and the isolates fromcattle feces are identified by band with position 342 bp. The specific bands are considered as markers inorder to know the source of E. coli O157:H7 fastly.
Keywords: E. coli O157:H7, RAPD, genetic marker, zoonoses